12-3(x-2)=4x-(x+3)

Simple and best practice solution for 12-3(x-2)=4x-(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-3(x-2)=4x-(x+3) equation:


Simplifying
12 + -3(x + -2) = 4x + -1(x + 3)

Reorder the terms:
12 + -3(-2 + x) = 4x + -1(x + 3)
12 + (-2 * -3 + x * -3) = 4x + -1(x + 3)
12 + (6 + -3x) = 4x + -1(x + 3)

Combine like terms: 12 + 6 = 18
18 + -3x = 4x + -1(x + 3)

Reorder the terms:
18 + -3x = 4x + -1(3 + x)
18 + -3x = 4x + (3 * -1 + x * -1)
18 + -3x = 4x + (-3 + -1x)

Reorder the terms:
18 + -3x = -3 + 4x + -1x

Combine like terms: 4x + -1x = 3x
18 + -3x = -3 + 3x

Solving
18 + -3x = -3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
18 + -3x + -3x = -3 + 3x + -3x

Combine like terms: -3x + -3x = -6x
18 + -6x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
18 + -6x = -3 + 0
18 + -6x = -3

Add '-18' to each side of the equation.
18 + -18 + -6x = -3 + -18

Combine like terms: 18 + -18 = 0
0 + -6x = -3 + -18
-6x = -3 + -18

Combine like terms: -3 + -18 = -21
-6x = -21

Divide each side by '-6'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| 1/8+5/8 | | 2x-=17 | | -7/3-(-2/3) | | 5x+27=2x+63 | | 10x+5=0 | | 4y^2+x+20y-12=0 | | 15-221-33-21 | | -5x/7-8 | | 30x-0.02x*2-50=0 | | c=30x-0.02x*2-50 | | -5/7-8-7 | | 10+g/-9=12 | | -25+t/2=50 | | table= | | 2x(x+4)=396 | | 4f+6=8t-14 | | 0=x^2-x-144 | | 2x^3-4x^2-6x=0 | | -2(w+(-6))=8w | | f/2-22=48 | | 7x+1.75=4x+3.10 | | 3b^2+12b+1=3 | | 18-3x=27 | | a/-8+15=23 | | N^2-16n+48=-9 | | 7+1.75x=4+3.10x | | X^2+14x-38=8 | | 41=6m-7 | | 2x^2+8x+14=8 | | z-9z=4z-6-z | | 55=-7y+6 | | 4p^2+16p-23=-9 |

Equations solver categories